0465 Association Between Physical or Sexual Abuse and Sleep Reactivity in Patients with Insomnia. (27th May 2020) - Drake, C L; Cheng, P; Kalmbach, D; Roth, T; Sagong, C; Arnett, L
Abstract: Introduction: Physical and sexual abuse are common and have demonstrated associations with insomnia. A common factor predisposing individuals to the development of insomnia is sleep reactivity, yet no studies have determined the relationship between sleep reactivity and physical and/or sexual abuse. Methods: Patients with DSM-5 insomnia disorder (N = 658; 519 F; mean age = 45.03) participated in an online randomized controlled trial of behavioral treatment of insomnia. Participants completed the Insomnia Severity Index (ISI), Ford Insomnia Response to Stress Test (FIRST), and demographic information at baseline. Abuse history was assessed with a single 4-choice item asking participants if they had a history of physical or sexual abuse. One-way analysis of variance was used to determine the level of sleep reactivity in each of the 4 abuse groups (none, physical, sexual, both) controlling for insomnia (ISI). Post-hoc analyses also compared differences in self-reported difficulties falling and staying asleep. Results: Compared to those with no abuse history (n = 465), patients who reported both physical and sexual abuse (n = 50) had significantly elevated FIRST scores (p < .001). Results remained significant after controlling for severity of insomnia, age, and gender. Post-hoc analyses showed group differences in sleep onset latency but not wake after sleep onset. Conclusion: Combined physical and sexual abuse are associated with higher levels of sleep reactivity to stress, and that the effects may be most prominent for difficulties falling asleep and not sleep maintenance. Prospective studies are needed to determine the potential effects of abuse on sleep reactivity, and whether sensitization of the sleep system to stress constitutes an etiological pathway in the development of insomnia disorder in survivors of abuse. Future work should also investigate potential overlapping biological markers of abuse and sleep reactivity. Support: This study was funded by the Robert Wood Johnson Foundation (PI: Drake).